Respuesta :

I'd prefer to see you do as much as you can towards solving these problems yourself before asking for help.

-32-8m=-4(2m+8) becomes    -32-8m=-8m-32 through multiplication.

When you have an outcome like this, that is, an equation that is true for all values of m, then the problem has infinitely many solutions.



-4(y-2)=2(-2+7)
Multiply out 
-4(y-2)  and then multiply out   2(-2+7).  You should obtain:

-4y + 8 = -4 + 14.  Note that you could evaluate 2(-2+7) by doing the work inside parentheses first, obtaining 5, and then by mult. this result by 2, obtaining 10.

Then -4y + 8 = 10.  Subtracting 8 from both sides,   -4y = 2, and  y = -1/2